Uji mikrobiologis susu sapi perah Friesh Holland : tinjauan dari sistem manajemen sanitasi yang berbeda pada sapi perah - Banamtuan, Nikson Feki; Handayani, Sri; Suroto, Karunia Setyowati (Universitas Tribhuwana Tunggadewi, 2018)
The purpose of this study is to determine the total number of Plate Count and MPN E.Koli on milk dairy Friesh Holland The experimental method was experimental by using a randomized block design with 6 treatments of 3 replications so that there were 18 experimental units consisting of P1 = (A1: river water + C1: hand washing rod + S1: udder and nipple washed) P2 = (A1: water + C2: washing hands + S1: udder and nipple in washing) P3 = (A2: well water + C1: hand washed + S1: udder and nipple washed) P4 = (A2: well water + C1: rouge not washing hands + S2: udder and nipple washed) P5 = (A3: water PDAM + C1: hand washing basin + S1: udder and nipple washed) P6 =(A3: water PDAM + C2: hand wash washed + S2: udder and nipple not washed). The variables observed in this research are Total Plate Count and MPN E.Koli Analysis of total plate count and MPN e.coli using analysis of variance (ANOVA) based on the results of this study it can be concluded that the sanitation management system to the highest total count count is found in the treatment of 1 (P1 = (A1 + C1 + S2) with the Total Plate Count 10.5x107 ± 0.59b while the highest MPN E.Koli at treatment (P1 = (A1 + C1 + S2) with MPN value 3.03 mpn / ml. Tujuan penelitian ini adalah untuk mengetahui jumlah Total Plate Count dan Most Probable Number Escherichia coli pada susu sapi perah Friesh Holland. Metode penelitian ini bersifat eksperimen dengan menggunakan rancangan acak kelompok dengan 6 perlakuan 3 ulangan perlakuan meliputi P1= (A1 : air sungai + C1: pemerah tidak mencuci tangan + S1: ambing dan putting dicuci) P2 = (A1: air sungai + C2: pemerah mencuci tangan + S1: ambing dan putting di cuci) P3: (A2 : air sumur +C1: pemerah tidak mencuci tangan + S1: ambing dan putting dicuci) P4 = (A2 : air sumur + C1: pemerah tidak mencuci tangan + S2 : ambing dan putting tidak dicuci) P5 = (A3 : air PDAM + C1: pemerah tidak mencuci tangan + S1: ambing dan putting dicuci) P6 = (A3: air PDAM + C2: pemerah mencuci tangan + S2: ambing dan putting tidak dicuci). Hasil penelitian ini adalah jumlah Total Plate Count yang meliputi perlakuan: P1=10,5x107 cfu/ml. P2 = 8,7x105cfu/ml. P3 = 8,6x105 cfu/ml. P4 = 8,7x105cfu/ml. P5 = 8,6x105cfu/ml. P6 = 8,5x105cfu/ml dan MPN E.koli yang meliputi perlakuan: P1=3,03 mpn/ml. P2=2,02 mpn/ml. P3=0 mpn/ml. P4=1,92 mpn/ml. P5=0 mpn/ml. P6=1,83 mpn/ml.